Pengaruh Pelatihan dan Kompetensi Terhadap Kinerja Karyawan di Divisi Software Laboratory Center (SLC) Universitas Bina Nusantara Kampus Anggrek Jakarta - Indriyani; Rani (Jurnal Mnajemen | Ekonomi | Akuntansi, 2025)
To determine the success and success of the company is the performance of employees, one that affects employee performance is training and competence. This study aims to analyze the impact of training and competence on employee performance in the Software Laboratory Center (SLC) division of Bina Nusantara University, Anggrek Campus Jakarta. The data used in the study used quantitative methods with data collection through questionnaires and distributed to employees of the Software Laboratory Center (SLC) division of Bina Nusantara University, Anggrek Campus Jakarta. The population of this study amounted to 65 respondents with non-probability respondents using saturated sample technique. This study presents the results of Training (X1) has no partial influence and significance on employee performance (Y) obtaining a t-count value of 1.756 < t-table 1.999 with a significant level of 0.084 > 0.05. Conversely, Competence (X2) has a positive and significant effect partially on employee performance (Y), with a t_count value of 5.945> t_table 1.999 with a significant level of <0.001 <0.05. For simultaneous F test results state that training (X1) and competence (X2) have a positive and significant impact simultaneously on employee performance (Y), with a value of F_hitung 54.848 l> F_tabel 3.14 and a significant level of <0.001 <0.05.